2020
DOI: 10.1186/s13047-020-00386-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and outcomes in middle‐aged patients with diabetic foot ulcers: a retrospective cohort study

Abstract: Background: Although ageing could increase the risk of delayed healing in diabetic foot ulcers (DFUs) patients, data from middle-aged patients remains greatly limited. The purpose of this study was to explore the clinical phenotypes, outcomes and predictive factors of DFU in middle-aged patients. Methods: A retrospective cohort study conducted with 422 consecutive inpatients with DFUs who visited our hospital between May 2010 and September 2017; participants were recruited and assigned according to age to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…But the literature on this topic is very limited, and to our knowledge, this is the first study to address the question. We were unable to find any previous published investigations on the role of immunosuppressive conditions beyond those specifically associated with diabetes in DFI patients, except in selected situations, such as those undergoing renal dialysis 4,5 or having a renal transplant, 6 or addressing risk factors for diabetic foot ulcers 5,7 or mortality. 4 Zou and Wukich reported that diabetic patients with solid transplant have no increased risk for nosocomial DFI after foot surgery (odds ratio 0.5, 95%CI 0.1-3.1).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…But the literature on this topic is very limited, and to our knowledge, this is the first study to address the question. We were unable to find any previous published investigations on the role of immunosuppressive conditions beyond those specifically associated with diabetes in DFI patients, except in selected situations, such as those undergoing renal dialysis 4,5 or having a renal transplant, 6 or addressing risk factors for diabetic foot ulcers 5,7 or mortality. 4 Zou and Wukich reported that diabetic patients with solid transplant have no increased risk for nosocomial DFI after foot surgery (odds ratio 0.5, 95%CI 0.1-3.1).…”
Section: Discussionmentioning
confidence: 98%
“…4 Zou and Wukich reported that diabetic patients with solid transplant have no increased risk for nosocomial DFI after foot surgery (odds ratio 0.5, 95%CI 0.1-3.1). 6 We examined definitions of chronic, enhanced immunosuppression both including and excluding alcohol abuse, 5,7 and the findings were the same. We undertook this assessment because of the high prevalence of elevated alcohol consumption among our DFI population (243/1,013; 24%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, there was no association between the treatment responses and the potency assay data of the applied cells (Additional file 1: Table S4), which indicates that the specified threshold acceptance values for product release are strong enough to guarantee proper biological activity. When comparing potential patient-related negative predictors for DFU healing such as greater wound surface area [101][102][103][104][105][106] and patient characteristics including older patient age [106][107][108], male gender [104,109], very high [110] or very low [108] body mass index, lower ankle-brachial index [109] and lower hemoglobin A1c [111], there were no significant differences between the responders and the non-responders that seem to have contributed to failure of treatment response (Fig. 8A).…”
Section: Discussionmentioning
confidence: 99%